2010
DOI: 10.1007/s11999-010-1427-0
|View full text |Cite
|
Sign up to set email alerts
|

The Fate of Grafting Acetabular Defects During Revision Total Hip Arthroplasty

Abstract: Background Acetabular defects are frequently grafted during revision THA. Previous studies using plain radiographs report high rates of graft incorporation. However, given plain radiographs underestimate osteolysis, it is unclear whether plain radiographs adequately reflect graft fill or incorporation. Questions/purposes We determined if (1) graft fill; or (2) incorporation (measured as graft-bone contact) differed with complete revision and grafting compared to liner exchange and grafting; (3) defect fill and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 32 publications
(45 reference statements)
0
20
0
Order By: Relevance
“…Fourth, our radiographic measurements were made using plain radiographs which may underestimate the preoperative size of defects and overestimate the degree of graft incorporation. Mall et al noted only 47% of graft fill and 36% graft healing in acetabular osteolytic defects following complete component revision using postoperative CT scan analysis [25]. This is much lower than previously reported rates of 90-100% using plain radiographs for analysis [26,40].…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Fourth, our radiographic measurements were made using plain radiographs which may underestimate the preoperative size of defects and overestimate the degree of graft incorporation. Mall et al noted only 47% of graft fill and 36% graft healing in acetabular osteolytic defects following complete component revision using postoperative CT scan analysis [25]. This is much lower than previously reported rates of 90-100% using plain radiographs for analysis [26,40].…”
Section: Discussionmentioning
confidence: 87%
“…Mehendale et al suggested that complete radiographic incorporation was only present with 40% of patients treated with irradiated bone [30]. Mall et al have recently reported a 30% average defect fill and 24% average bone healing rate using CT scans for evaluation, with lower graft incorporation rates among patients treated with impaction grafting behind retained acetabular components than during cases where component revision had been accomplished [25].…”
Section: Discussionmentioning
confidence: 99%
“…In patients with osteolysis detected prior to acetabular component loosening, retention of the acetabular component has multiple advantages, including decreased morbidity and preservation of pelvic bone stock [2][3][4] . Structurally stable lytic defects can be addressed with bonegrafting through screw holes or around the periphery of a wellfixed acetabular component 5 . Aggressive debridement and curettage of these lesions in combination with exchange of the Disclosure: None of the authors received payments or services, either directly or indirectly (i.e., via his or her institution), from a third party in support of any aspect of this work.…”
Section: Authorsmentioning
confidence: 99%
“…polyethylene liner to a highly cross-linked polyethylene liner may be sufficient to halt the lytic process [5][6][7] . Proponents of this approach reserve full acetabular revision for patients with a loose or malpositioned acetabular component.…”
Section: Authorsmentioning
confidence: 99%
See 1 more Smart Citation